Axis and contents of Prophetical Commendatory Poems at Granada Kingdom) E (635 ـ897 - Salman, Nabeel (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
A attended reading of poem collection in Granada Kingdom, will show us, the extension area of Prophetical Commendatory Poems, at that stage from lately life of Islamic State in Andalusia. Its sure that, the sincere, faithful, extensive love of the prophet Mohammad (god pray on him) , the distant from holy places, longing and burning desire to this places, recognizing the more misdeeds, self admonishing and punishing, more thanking and pardoning, and also the political situation in which, Andalusia turned over to dropping ,because of its governors policy and enemies wise, all of these and others, contributed in extending of Prophetical Commendatory Poems area, all of which glorifying the prophet Mohammad(god pray on him), as he is the creation Sirs, the best human, a luminance being, as well his concomitants have had the place in Granada poetry, as they were supporting and sustaining the prophet and the message. Granada’s Prophetical Commendatory Poems came, with many objectives and subjects, in the same manner as the verses of classic Arabian Poetry, which were clearly affected by Prophetical Commendatory Poets, and contrary poems were the attribute of the poetical objectives of that period. All of these were associated for Granadian poets with full trust in hopes, which represented by Chosen Mohammad(god pray on him) and his companions, in encouraging Muslims of Andalusia , response, pardoning, victory and wins.